A Prospective Audit, Investigating Visual Acuity in Older Adults Living in Sheltered Accommodation - Johnson, Caitlin (2012)
Aim This study‟s aim was to conduct an audit of visual acuity (VA) against the British Geriatrics Society‟s recommendations (BGS, 2010), in order to establish the level of eye services received by older adults living in sheltered accommodation. Objectives included examining whether participants had appropriate access to eye services and attended annual eye examinations for screening of visual impairment (VI). Background VI is one of the leading causes of morbidity in the elderly population (Chen and Thomas, 2010). An estimated 1.6 million-2.2 million adults aged 65 years and over are visually impaired in the UK (Charles, 2007). In particular the BGS (2010) identifies preventable or treatable VI as a major problem. VI has been associated with infrequency of ophthalmic visits (Abdelhafiz and Austin, 2003), and reduced functional status, predisposing the elderly to falls (Wun et al, 1997; Smeeth and Iliffe, 1998) Method A prospective audit was conducted, including 28 participants 60 years and older. All information was participant-reported and VA results were obtained using a standard six metre Snellen chart. Results were converted to the LogMAR format for statistical analyses. Results 100% of participants stated they had access to eye care services, however only 61% of participants had visited an optometrist for an eye examination within the past year as per recommendations. 7% of participants had VI as defined by a VA of VII 6/12 or worse. Non-compliance with wearing glasses was identified in 25% of participants and was shown to significantly worsen VA results. Conclusion Residents in sheltered accommodation are one group of older adults with a low prevalence of VI compared to the population as a whole. However older adults still need to be educated on the importance of annual aye examinations and compliance with wearing glasses to reduce the prevalence of treatable VI